Nursing students’ perception of a web-based intervention to support learning - Koch, J.; Andrew, S.; Salamonson, Y.; Everett, B.; Davidson, Patricia (Churchill Livingstone, 2010)
Tailoring information to the needs of the learner is an important strategy in contemporary education settings. Web-based learning support, informed by multimedia theory, comprising interactive quizzes, glossaries with audio, short narrated Power Point® presentations, animations and digitised video clips were introduced in a first year Bachelor of Nursing biological sciences subject at a university in metropolitan Sydney. All students enrolled in this unit were invited to obtain access to the site and the number of hits to the site was recorded using the student tracking facility available on WebCT, an online course delivery tool adopted widely by many educational institutions and used in this study. Eighty-five percent of students enrolled in the subject accessed the learning support site. Students’ perception of the value of a learning support site was assessed using a web-based survey. The survey was completed by 123 participants, representing a response rate of 22%.Three themes emerged from the qualitative data concerning nursing students’ perception of the web-based activities: ‘enhances my learning’, ‘study at my own pace’, and ‘about the activities: what I really liked/disliked’. Web-based interventions, supplementing a traditionally presented nursing science course were perceived by students to be beneficial in both learning and language development. Although students value interactive, multimedia learning they were not ready to completely abandon traditional modes of learning including face-to-face lectures. The findings of this study contribute to an understanding of how web-based resources can be best used to support students’ learning in bioscience.